Civil procedure - Mohamed, Duryana (CLJ Publication, 2014)
INTRODUCTION Civil procedure prescribes methods of enforcing rights or obtaining redress for their invasion. It is important because it allows parties in dispute to claim and enforce their rights under the laws. Civil procedure also regulates procedural rules and proceedings as well as ensuring the parties involved follow the correct court rules and procedures. Prior to filing a civil suit, a person or any corporate body has to ensure that several requirements are fulfilled in order to avoid any irregularities in the proceedings. These requirements are also known as preliminary matters which among others include identifying the cause of action, the appropriate court that has the jurisdiction to hear the case, the time limit to file the claim, the parties to be named in the proceedings and other relevant proceedings.